Reconstruction of a massive abdominal wall defect after colon cancer surgery using bilateral thoracoabdominal flaps and a vertical rectus abdominis myocutaneous flap: a case report - Li, Shuo; Zhang, Zhi; Gao, Chongqing; Wang, Tao; Zhang, Zhen; Wang, Zikang; Zhang, Guixiang; Wang, Gangcheng (Frontiers in Oncology, 2025)
A 35-year-old woman presented with a local recurrence at the stoma site three months after Hartmann’s procedure for sigmoid colon cancer. In the subsequent months, the tumor exhibited rapid progression, with direct invasion into the abdominal wall. Her clinical course was characterized by persistent pain, fever, foul odor, and defecation disorder. The substantial disease burden ​​confined her to bed, leaving her unable to care for her two young children​​. Following a multidisciplinary team (MDT) evaluation, she was deemed a candidate for reoperative surgery. The procedure comprised en bloc resection of the recurrent tumor, followed by restoration of bowel continuity with a primary colorectal anastomosis and immediate abdominal wall reconstruction. The patient’s postoperative recovery was uneventful, with a marked improvement in quality of life. This case highlights the critical role of flap-based reconstruction in managing complex abdominal wall defects.